From phone access to food markets: Is mobile connectivity transforming West-African livelihoods? - Joël Cariolle; David A. Carroll (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
This paper investigates the impact of mobile connectivity on food market prices and household demand for food products in the West African Economic and Monetary Union (WAEMU) region. Leveraging data from harmonized World Bank LSMS household surveys across eight WAEMU countries, this study includes 59,319 households and 146 food products across 4,983 enumeration areas, with data gathered in 2018-2019. By using exposure to lightning strikes as an instrumental variable for cell tower coverage, we find that mobile connectivity reduces food price dispersion by spurring food prices catch-up in rural areas. Greater market demand for food products and lower reliance on self-consumption of food produced by rural households appear to be the drivers of this observed convergence in food price. Additionally, enhanced financial inclusion through mobile money and diversification of income sources through off-farm and non-agricultural activities are identified as key enablers of these observed changes. Overall, these results suggest that the digitalization of rural areas stimulates the transition from a subsistence to a market economy, thereby accelerating rural transformations, albeit with the added risk of leaving unconnected households behind.
Keywords: O13; O33; Q11; Q13; 330; Connectivity; digital; mobile phone; mobile money; agricultural markets; household; food consumption